Knowledge, Attitude and Practice of Self-Medication among Undergraduate Pharmacy Students in University Royal College of Medicine Perak - Nur Syafiqah Abdul Fattah; Aina Amanina Abdul Jalil; Nor Safwan Hadi Nor Afendi (Asian Journal of Medicine & Health Sciences, 2022)
Background: Pharmacy students who practise self-medication are equally exposed to its hazards like the general population. It should be opted for only in the appropriate situations and not inadvertently. Proper education regarding the safe practice of self-medication should be provided to all pharmacy students. This study aims to investigate knowledge, attitude, and practice (KAP) of self-medication among undergraduate pharmacy students in Universiti Kuala Lumpur Royal College of Medicine Perak (UniKL RCMP). Methods: A cross- sectional study involving 109 students was conducted by distributing voluntary self-administrated online questionnaire. The data obtained were expressed as frequency (n), percentage (%) and mean to determine the level of respondents’ KAP on self-medication. Chi-square test was also used to identify the association between respondents’ demographic characteristics with the level of knowledge and practice on self-medication. P-value <0.05 was considered statistically significant. Results: Findings from this study showed that most of the respondents had a good level of knowledge (62.40%) and neutral attitude (69.70%) towards self-medication practice. It was also reported that most of the respondents (99.10%) practised self-medication and 90.83% of them self-medicate because of minor illnesses. Analgesics (77.98%) was the major type of drug class involved in self-medication followed by antihistamine (71.56%) and vitamins or supplements without prescription (62.39%). Conclusion: Knowledge of pharmacy students on self-medication practice increases with each passing year and semester of study. This study can provide valuable insight on the level of awareness of pharmacy students towards self-medication while helping the university to prepare them to provide reliable consultation in real-life practice.